Evaluación de tres tratamientos pre germinativos con cuatro tipos de sustratos y dos bioestimulantes en la etapa de germinacion y desarrollo de la especie nativa pumamaqui (oreopanax ecuadorensis) en el Vivero forestal Belisario Quevedo, sector Illuchi, provincia de Cotopaxi - 2014 - Bermeo Heredia, Carlos Santiago (2015)
The objectives in this researching were to: Evaluate and select the best treatment for pregerminativePumamaqui seed, with best substrate for germination and development of Pumamaqui, evaluate and select the bioestimulante that promotes germination Pumamaquiwith an economical analysis of treatments. Design Randomized Complete (DBCA) was applied Blocks factorial arrangement 3x4x2 + 1. Three factors were applied to study as pregerminative: hot water 100 ° C, Alcohol: 5% Chlorine: 20%, the second factor was substrates b1: 50% Black Earth, Pomina 30%, 20% organic matter. b2: 50% Black Earth, 30% Arena. 20% Organic Matter, b3: 30% Black Earth, 30% sand, 40% Organic Matter, b4: 50% Black Earth, 50% Arena. The factor c was: c1: Raizal, c2: Evergreen. The evaluated variable were: days to emergence, emergence percentage, silver height and number of leaves at 15, 30, 45, 60, 75, 90, 105 and 120 days. From the results obtained pregerminativeThe best treatment for Pumamaqui seed was taken: a2: Alcohol 5%; which scored lower precocity in days to 48.67 days emergency; Emergency higher percentage 91.66%. The best substrate for the germination and development was Pumamaqui b3: component which were 30% topsoil, 30% sand and 40% organic matter, the obtained lower emergency 47.09 days, plant height greater culminating 4 68 cm at 120 days, more leaves with 6.37 at 120days. The bio-stimulant had much the same effect as the raizal green ever since to perform statistical analyzes showed no significance interpret what the two had similar effects.